Complete Genomic Analysis of a Salmonella enterica Serovar Typhimurium Isolate Cultured From Ready-to-Eat Pork in China Carrying One Large Plasmid Containing mcr-1 - Wang, Wei; Baloch, Zulqarnain; Zou, Mingyuan; Dong, Yinping; Peng, Zixin; Hu, Yujie; Xu, Jin; Yasmeen, Nafeesa; Li, Fengqin; Fanning, Séamus (Frontiers in Microbiology, 2018)
One mcr-1-carrying ST34-type Salmonella Typhimurium WW012 was cultured from 3,200 ready-to-eat (RTE) pork samples in 2014 in China. Broth dilution method was applied to obtain the antimicrobial susceptibility of Salmonella Typhimurium WW012. Broth matting assays were carried out to detect transferability of this phenotype and whole-genome sequencing was performed to analyze its genomic characteristic. Thirty out of 3200TE samples were positive for Salmonella and the three most frequent serotypes were identified as S. Der by (n = 8), S. Typhimurium (n = 6), and S. Enteritidis (n = 6). One S. Typhimurium isolate (S. Typhimurium WW012) cultured from RTE prepared pork was found to contain the mcr-1 gene. S. Typhimurium WW012 expressed a level of high resistance to 7 different antimicrobial compounds in addition to colistin (MIC = 8 mg/L). A single plasmid, pWW012 (151,609-bp) was identified and found to be of an IncHI2/HI2Atype that encoded a mcr-1 gene along with 6 additional antimicrobial resistance genes. Plasmid pWW012 contained anIS30-mcr-1-orf-orf-IS30composite transposon that can be successfully transferred to E. coli J53. When assessed further, the latter demonstrated considerable similarity to three plasmids pHYEC7-mcr-1, pSCC4, and pHNSHP45-2, respectively. Furthermore, plasmid pWW012 also contained a multidrug resistance (MDR) genetic structure IS26-aadA2-cmlA2-aadA1-IS406-sul3-IS26-dfrA12-aadA2-IS26, which showed high similarity to two plasmids, pHNLDF400 and pHNSHP45-2, respectively. Moreover, genes mapping to the chromosome (4,991,167-bp) were found to carry 28 mutations, related to two component regulatory systems (pmrAB, phoPQ) leading to modifications of lipid A component of the lipopolysaccharide structure. Additionally, one mutation (D87N) in the quinolone resistance determining region (QRDR) gene of gyrA was identified in this mcr-1 harboring S. Typhimurium. In addition, various virulence factors and heavy metal resistance-encoding genes were also identified on the genome of S. Typhimurium WW012. This is the first report of the complete nucleotide sequence of mcr-1-carrying MDR S.Typhimurium strain from RTE pork in China.